Firm Value in the Sustainability Era: an Analysis of Green Accounting, ROA, and Firm Size - Putri, Zahra Vania; Wardhani, Nurhastuty Kesumo (Media Bisnis, 2025)
This study aims to obtain empirical evidence on the influence of green accounting, profitability, and firm size on firm value. The main issue addressed is the inconsistency of previous findings regarding the determinants of firm value, particularly in Non-Cyclicals and Cyclicals sectors. The population includes companies from both sectors listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 21 companies with a total of 84 observations. Data were analyzed using multiple linear regression. The results show that profitability has a significant positive effect on firm value, indicating that earnings performance is a key indicator for investors in evaluating company prospects. Meanwhile, green accounting and firm size do not significantly affect firm value. These findings imply that environmental cost reporting is not yet considered a critical factor by investors in their investment decisions. Therefore, companies should consider adopting a more comprehensive sustainability reporting strategy to enhance investor perception and long-term value.